Lithium ion battery electrolyte combination, secondary electrolyte injection process and lithium ion battery
By adjusting the content of vinylene carbonate in the secondary injection electrolyte and the spacing of graphite layer, combined with the combination of single particles and secondary particle graphite, the problem of improving the performance of lithium-ion batteries in the prior art is solved, and significant improvements in the magnification, circulation and low-temperature performance are achieved.
Patent Information
- Application Number
- CN202411728380.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-04
AI Technical Summary
The prior art is difficult to effectively improve the performance of lithium-ion batteries through the combination of single-particle graphite and secondary-particle graphite and the secondary liquid injection process, especially in terms of magnification, circulation and low-temperature performance.
By adjusting the content of vinylene carbonate in the two injection electrolytes, combining the ratio of graphite single particles and secondary particles, the content of negative electrode active materials, and the layer spacing between graphite particles and carbon cladding layers, a lithium-ion battery electrolyte combination and secondary injection process were formulated.
The significant improvement in rate performance, high-temperature storage and circulation performance of lithium-ion batteries has been achieved, and the increase in SEI film thickness and degradation of battery performance caused by conventional injection of high-content VC electrolytes are avoided.
Smart Images

Figure CN119560631A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion batteries, relates to a method for injecting a lithium ion battery, and specifically relates to a lithium ion battery electrolyte combination, a secondary injection process and a lithium ion battery. Background Art
[0002] Lithium-ion batteries have advantages such as high safety, long service life and low cost, but they still have problems with fast charging capability and poor low-temperature performance. In order to cope with the increasingly high usage requirements, lithium-ion batteries currently use the process of compounding single negative electrode particles with secondary particles and secondary injection in pursuit of performance improvement. The carbon coating layer of the graphite negative electrode is closely related to the electrolyte. Lithium-ion batteries will undergo solvation and desolvation of lithium ions during charging and discharging. Using the high-layer spacing carbon coating layer to desolvate lithium ions can greatly increase the desolvation rate of lithium-ion batteries, thereby improving the rate performance of the negative electrode. Vinylene carbonate (VC) is the main additive in the electrolyte of lithium iron phosphate batteries. It can form a stable SEI film on the surface of the negative electrode and improve the high temperature, rate and cycle performance of the battery. However, too high a VC content will increase the thickness of the SEI film, resulting in a high DC internal resistance (DCR) of the battery, which will lead to a decrease in the rate and low-temperature performance of the battery. The content of vinylene carbonate in the first injection electrolyte is limited to a smaller value, and a high proportion of vinylene carbonate is added to the second injection electrolyte after a stable SEI film is formed after the battery formation is completed, so as to increase the content of vinylene carbonate in the total electrolyte of the lithium-ion battery, so that the lithium-ion battery has an electrolyte that does not affect the SEI thickness but retains a high content of VC after injection, thereby improving the performance of the lithium-ion battery.
[0003] At present, there is no record of the use of a negative electrode active material compounded of single-grain graphite and secondary-grain graphite (especially compounded after single-grain graphite and secondary-grain graphite are separately carbon-coated) in combination with a secondary injection process. According to the inventor's research, vinylene carbonate, as a key additive in the secondary injection electrolyte, has a great influence on the overall performance of the battery in its usage amount in the secondary injection electrolyte. It is difficult to better improve the performance of lithium-ion batteries by using the existing secondary injection process of vinylene carbonate in combination with a negative electrode active material compounded of single-grain graphite and secondary-grain graphite (especially compounded after single-grain graphite and secondary-grain graphite are separately carbon-coated). Summary of the invention
[0004] In order to overcome the deficiencies in the prior art, the purpose of the present invention is to provide a lithium ion battery electrolyte combination, a secondary injection process and a lithium ion battery. The present invention unexpectedly discovered through research that when a lithium ion battery using single-particle graphite and secondary-particle graphite as negative electrode active materials is subjected to secondary injection, the content of vinylene carbonate in the electrolyte of the two injections is related to the ratio of single-particle graphite and secondary-particle graphite, the content of negative electrode active materials, the interlayer spacing of the graphite particles themselves, and the interlayer spacing of the carbon coating layers. The content of vinylene carbonate in the electrolyte of the two injections is adjusted according to the ratio of single-particle graphite and secondary-particle graphite, the content of negative electrode active materials, the interlayer spacing of the graphite particles themselves, and the interlayer spacing of the carbon coating layers, so as to better improve the performance of the lithium ion battery.
[0005] In order to achieve the above object, the technical solution of the present invention is:
[0006] In a first aspect, a lithium-ion battery electrolyte combination is provided, wherein the lithium-ion battery electrolyte combination is used for secondary injection of a lithium-ion battery, wherein the negative electrode active material of the lithium-ion battery is carbon-coated single-grain graphite and carbon-coated secondary-grain graphite; the combination includes a first electrolyte for the first injection and a second electrolyte for the second injection; the first electrolyte and the second electrolyte both contain a lithium salt, a solvent and an additive, wherein the additive includes vinylene carbonate;
[0007] The calculation formula of the mass content of vinylene carbonate (W1) in the first electrolyte is as follows:
[0008]
[0009] The calculation formula of the mass content of vinylene carbonate (W2) in the second electrolyte is as follows:
[0010]
[0011] Among them, a is the ratio of the mass of single graphite particle to the total mass of single graphite particle and secondary graphite particle, b is the mass fraction of negative electrode active material in the negative electrode slurry when preparing the negative electrode of lithium ion battery, d1 is the interlayer spacing of graphite particles themselves, d2 is the interlayer spacing of carbon coating, and W1<W2.
[0012] In a second aspect, a secondary liquid injection process is provided, wherein the above-mentioned lithium-ion battery electrolyte combination is provided, a first electrolyte is injected into the lithium-ion battery, and then a first standing is performed, and then formation is performed, and then a second standing is performed, and a second electrolyte is injected into the lithium-ion battery.
[0013] In a third aspect, a lithium-ion battery adopts the above-mentioned secondary injection process when injecting electrolyte.
[0014] The beneficial effects of the present invention are:
[0015] First, in the lithium-ion battery electrolyte combination of the present invention, the VC content in the first electrolyte is lower than the VC content in the second electrolyte, the first electrolyte contains less vinylene carbonate, and the battery cell will be formed after the first electrolyte is injected, and a SEI film of normal thickness can be generated, which does not affect the DCR value of the battery. The second electrolyte contains more vinylene carbonate, and the vinylene carbonate content in the total electrolyte in the lithium-ion battery is high after two injections. The high content of vinylene carbonate can allow the battery to obtain excellent rate and cycle performance. On the contrary, the conventional single-injection high-content vinylene carbonate electrolyte will not only increase the SEI film thickness and increase the DCR value, but will also reduce the cycle performance in the subsequent period.
[0016] Secondly, the formation of lithium-ion batteries and subsequent charging and discharging will be affected by the morphology of negative electrode particles, the size of the spacing between negative electrode graphite layers, the size of the spacing between carbon coating layers, and the SEI film. The present invention combines the mutual influence of the parameters of the negative electrode particle morphology, the size of the spacing between negative electrode graphite layers, the size of the spacing between carbon coating layers, and the SEI film to generate the VC content formula in the first and second injection electrolytes. The new electrolyte obtained using the content formula can perfectly fit the lithium battery chemical system, thereby improving battery performance. The traditional secondary injection volume does not combine the single and secondary particle interlayer spacing, but the size of the VC content directly affects the thickness of the SEI film, and the SEI film thickness and the size of the spacing between carbon coating layers jointly affect the electrical properties of the lithium battery, so the performance needs to be improved.
[0017] In summary, the lithium-ion battery prepared by the lithium-ion battery electrolyte combination and the secondary injection process provided by the present invention has greatly improved rate performance, high-temperature storage, and cycle performance compared to ordinary lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0019] Figure 1 It is a comparison diagram of rate discharge curves of Example 1, Comparative Example 1-1, and Comparative Example 1-2 of the present invention;
[0020] Figure 2 It is a comparison diagram of the cycle curves of Example 1, Comparative Example 1-1 and Comparative Example 1-2 of the present invention;
[0021] Figure 3 It is a comparison diagram of rate discharge curves of Example 2 of the present invention, Comparative Example 2-1, and Comparative Example 2-2;
[0022] Figure 4It is a comparison diagram of the cycle curves of Example 2, Comparative Example 2-1 and Comparative Example 2-2 of the present invention;
[0023] Figure 5 It is a comparison diagram of rate discharge curves of Example 3, Comparative Example 3-1 and Comparative Example 3-2 of the present invention;
[0024] Figure 6 It is a comparison chart of the cycle curves of Example 3, Comparative Example 3-1 and Comparative Example 3-2 of the present invention. DETAILED DESCRIPTION
[0025] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0026] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0027] In view of the fact that it is difficult to better improve the performance of lithium-ion batteries after the existing secondary injection process of vinylene carbonate is combined with a negative electrode active material of single-grain graphite and secondary-grain graphite (especially single-grain graphite and secondary-grain graphite are respectively carbon-coated and then compounded), the present invention proposes a lithium-ion battery electrolyte combination, a secondary injection process and a lithium-ion battery.
[0028] A typical embodiment of the present invention provides a lithium-ion battery electrolyte combination, wherein the lithium-ion battery electrolyte combination is used for secondary injection of a lithium-ion battery, wherein the negative electrode active material of the lithium-ion battery is a carbon-coated single-grain graphite and a carbon-coated secondary-grain graphite; the combination includes a first electrolyte for the first injection and a second electrolyte for the second injection; the first electrolyte and the second electrolyte both contain a lithium salt, a solvent and an additive, wherein the additive includes vinylene carbonate;
[0029] The calculation formula of the mass content of vinylene carbonate (W1) in the first electrolyte is as follows:
[0030]
[0031] The calculation formula of the mass content of vinylene carbonate (W2) in the second electrolyte is as follows:
[0032]
[0033] Among them, a is the ratio of the mass of single graphite particle to the total mass of single graphite particle and secondary graphite particle, b is the mass fraction of negative electrode active material in the negative electrode slurry when preparing the negative electrode of lithium ion battery, d1 is the interlayer spacing of graphite particles themselves, d2 is the interlayer spacing of carbon coating, and W1<W2.
[0034] In some embodiments, the mass of the first electrolyte is 75-90% of the total mass of the first electrolyte and the second electrolyte.
[0035] In some embodiments, the ratio a of the mass of the single graphite particles to the total mass of the single graphite particles and the secondary graphite particles is 35 to 55%.
[0036] In some embodiments, when preparing the negative electrode of a lithium-ion battery, the mass fraction b of the negative electrode active material in the negative electrode slurry is 95-97%.
[0037] The lithium salt used in the present invention is a lithium salt commonly used in lithium-ion batteries. In some embodiments, the lithium salt is selected from at least one of lithium perchlorate (LiClO4), lithium tetrafluoroborate (LiBF4), lithium hexafluoroarsenate (LiAsF6), lithium hexafluorophosphate (LiPF6), lithium trifluoromethanesulfonate (LiCF3SO3), lithium bistrifluoromethanesulfonyl imide (C2F6LiNO4S2), and lithium bis(oxalatoborate) (C4BLiO8).
[0038] In some embodiments, the mass fraction of the lithium salt in the first electrolyte is 5-15%.
[0039] In some embodiments, the mass fraction of the lithium salt in the second electrolyte is 5-20%.
[0040] The solvent used in the present invention is a commonly used solvent in lithium-ion batteries. In some embodiments, the solvent is selected from at least one of ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), γ-butyrolactone (GBL), ethyl acetate (EA), methyl acetate (MA), methyl propionate (MP), propyl propionate (PP) or ethyl propionate (EP).
[0041] In some embodiments, the mass fraction of the solvent in the first electrolyte is 30-80%.
[0042] In some embodiments, the mass fraction of the solvent in the second electrolyte is 30-70%.
[0043] The additives used in the present invention also include non-vinyl carbonate additives commonly used in lithium-ion batteries. In some embodiments, the additives also include other additives, and the other additives are selected from at least one of vinyl sulfate (DTD), vinyl sulfite (ES), methylene disulfonate (MMDS), 1,3-propane sultone (PS), tris(trimethylsilyl) phosphate (TMSP), fluoroethylene sulfate (FEC), fluorobenzene (FB), 1,4-butane sultone (BS), and tris(trimethylsilyl) borate (TMSB).
[0044] In some embodiments, the mass fraction of other additives in the first electrolyte is 0.1-6%.
[0045] In some embodiments, the mass fraction of other additives in the second electrolyte is 0.1-6%.
[0046] In some embodiments, the additive further includes a lithium salt additive, and the lithium salt additive is selected from at least one of lithium difluorooxalatoborate (LiODFB), lithium difluorobisoxalatophosphate (LiDFOP), lithium tetrafluorooxalatophosphate (LiOTFP), and lithium bis(fluorosulfonyl)imide (LiFSI).
[0047] In some embodiments, the mass fraction of the lithium salt additive in the second electrolyte is 1-8%.
[0048] Another embodiment of the present invention provides a secondary liquid injection process, providing the above-mentioned lithium-ion battery electrolyte combination, injecting a first electrolyte into the lithium-ion battery, then allowing it to stand for a first time, then performing formation, and then allowing it to stand for a second time, and then injecting a second electrolyte into the lithium-ion battery.
[0049] In some embodiments, the temperature of the first standing temperature is 40-45° C., preferably 44-45° C., and the time of the first standing temperature is 24-48 hours. High temperature standing temperature can improve the wetting effect of the positive and negative electrode sheets of the battery.
[0050] In some embodiments, the temperature of the second standing is 40-45°C, preferably 44-45°C, and the time of the second standing is 24-36 hours. High temperature standing can improve the wetting effect of the positive and negative pole pieces of the battery; at the same time, the battery cell is charged after formation, and standing at high temperature can allow some side reactions to proceed in advance. The subsequent second sealing and degassing of the battery will take away the gases generated by these side reactions, thereby improving the cycle performance.
[0051] A third embodiment of the present invention provides a lithium-ion battery, wherein the lithium-ion battery adopts the above-mentioned secondary injection process when injecting electrolyte.
[0052] In some embodiments, the positive electrode active material of the lithium-ion battery is lithium iron phosphate (LFP).
[0053] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in combination with specific embodiments and comparative examples.
[0054] Embodiment 1:
[0055] Make 5Ah lithium iron phosphate battery cells.
[0056] The positive electrode active material is LFP material, and the positive electrode formula is PVDF (polyvinylidene fluoride): SP (conductive carbon black SP): CNT (carbon nanotube): LFP = 2%: 1.5%: 0.5%: 96%. The positive electrode surface density is 200 ± 3g / m 2 , cold pressed to 2.4g / m 3 , and the positive electrode sheet is obtained after punching.
[0057] The negative electrode active material uses single-particle and secondary-particle composite graphite. The raw material is needle coke, which is first subjected to airflow milling (crushing) to obtain 5-10μm pretreated particles. The pretreated particles are stirred in a reactor at 250°C for 2h, and then continued to heat to 450°C, and stirred to obtain a material with a particle size of 10-20mm, that is, intermediate material one. The intermediate material one is mechanically ball-milled in a ball mill to produce material two with a particle size of 1-8.5μm, and material two is graphitized at 3000°C to obtain intermediate material three, which is single-particle graphite. Intermediate material three is mixed with asphalt in a mass ratio of 90:10, and the mixed material is reacted in a reactor at 600°C for 3h to obtain material four, which is single-particle and secondary-particle composite graphite. Both single-particle and secondary-particle graphite are coated with carbon. The carbon coating process is as follows: Material 4 is mixed with a liquid phenolic resin solution (phenolic resin 75wt%, emulsifier gelatin 4wt%, stabilizer sodium carboxymethyl cellulose 1wt%, calcium chloride 0.5wt%, chromium trichloride 0.5wt%, water 19wt%) at a mass ratio of 97:3, and reacted in a reactor at 1800℃ for 3h to obtain the final desired graphite. The negative electrode graphite D50 is 11μm (typical value) and the specific surface area is 1.75m 2 / g (typical value). Among them, the mass proportion of single-particle graphite a is 40%, and the mass proportion of secondary-particle graphite (1-a) is 60%; the interlayer spacing d1 of single-particle and secondary-particle graphite is 0.335nm, and the interlayer spacing d2 of carbon coating is 0.360nm; the negative electrode formula is SBR:SP:CMC:Gr=1.8%:1%:1.2%:96% (that is, the mass fraction b of negative electrode active material is 96%). The negative electrode surface density is 90±3g / m 2 , cold pressed to 1.55g / m 3 , and the negative electrode sheet is obtained after punching.
[0058] The mass ratio of the first electrolyte VC is W1=0.5*(1-(d1 / d2)) / (a / (1-a))=5%, and the total ratio is LiPF6:LiFSI:EC:EMC:DMC:VC:DTD:MMDS=12:5:30:25:20:5:1.5:1.5;
[0059] The mass ratio of the second electrolyte VC W2 = (1-(d1 / d2))*(100-b*100) = 28%, and the total ratio is LiPF6:EC:EMC:DMC:VC:LiODFB:PS = 12:25:20:10:28:2.5:2.5;
[0060] The total amount of electrolyte injection is 17.5g, the first electrolyte injection amount is 14g, and the second electrolyte injection amount is 3.5g;
[0061] When lithium-ion batteries are injected, the first electrolyte is injected in sequence. After the first electrolyte is injected, the battery is left standing at high temperature (45°C) for 48 hours, formed (conventional hot pressing formation, 45°C hot pressing - battery surface pressure 0.75MPa, left standing for 5 minutes, 0.02C charging for 6 hours, left standing for 5 minutes, 0.15C charging for 3 hours, end), left standing at high temperature (45°C) for 36 hours, and then injected with the second electrolyte.
[0062] Comparative Example 1-1:
[0063] The positive and negative electrode plates are the same as those in Example 1.
[0064] The electrolyte injection weight is consistent with that in the embodiment, which is 17.5 g.
[0065] The electrolyte ratio is
[0066] LiPF6:LiFSI:EC:EMC:DMC:VC:DTD:MMDS:LiODFB:PS=12:4:29:24:18:9.6:1.2:1.2:0.5:0.5.
[0067] In comparative example 1-1, the electrolyte is not injected for the second time, and all the electrolyte is injected after the battery cell is dried (from the specific quantities, it can be known that the weight of each component of the electrolyte in the comparative example is consistent with that in the embodiment).
[0068] Comparative Example 1-2:
[0069] The positive and negative electrodes are selected to be consistent with those in the embodiment;
[0070] The electrolyte injection weight is consistent with the embodiment, which is 17.5 g;
[0071] Comparative Example 1-2 adopts secondary injection, the injection amount of the first electrolyte is 14g, and the injection amount of the second electrolyte is 3.5g;
[0072] The first electrolyte ratio is
[0073] LiPF6:LiFSI:EC:EMC:DMC:VC:DTD:MMDS=12:5:33.5:25:20:1.5:1.5:1.5;
[0074] The second electrolyte ratio is
[0075] LiPF6:EC:EMC:DMC:VC:LiODFB:PS=12:25:30:10:18:2.5:2.5.
[0076] The battery electrical properties (including direct current resistance (DCR) (50SOC%, 2C discharge 10S), discharge capacity retention rate (4C current, discharge to 2.0V), high temperature storage recovery rate) and cycle performance (25°C, 1C charge and discharge, voltage range 2.0-3.65V) of the battery cells prepared in Example 1, Comparative Example 1-1 and Comparative Example 1-2 were tested (electrical performance refers to GB31486, cycle refers to GB31484), and the results are shown in the following table and Figures 1-2 shown.
[0077]
[0078]
[0079] From the comparison between the embodiment and the comparative example, it can be seen that the lithium-ion battery produced by the combination of the electrolyte combination of this embodiment and the secondary injection electrolyte process has greatly improved electrical performance and cycle compared with the lithium-ion battery produced by ordinary primary injection electrolyte and conventional secondary injection electrolyte.
[0080] Embodiment 2:
[0081] Make 5Ah lithium iron phosphate battery cells.
[0082] The positive electrode active material is LFP material, and the positive electrode formula is
[0083] PVDF:SP:CNT:LFP=2%:1.5%:0.5%:96%. The positive electrode surface density is 180±3g / m 2 , cold pressed to 2.5g / m 3 , and the positive electrode sheet is obtained after punching.
[0084] The negative electrode active material uses single-particle and secondary-particle composite graphite. The raw material is needle coke, which is first subjected to airflow milling (crushing) to obtain 5-10μm pretreated particles. The pretreated particles are stirred in a reactor at 250°C for 2h, and then continued to heat to 450°C, and stirred to obtain a material with a particle size of 10-20mm, that is, intermediate material one. The intermediate material one is mechanically ball-milled in a ball mill to produce material two with a particle size of 1-8.5μm, and material two is graphitized at 3000°C to obtain intermediate material three, which is single-particle graphite. Intermediate material three is mixed with asphalt in a mass ratio of 90:10, and the mixed material is reacted in a reactor at 600°C for 3h to obtain material four, which is single-particle and secondary-particle composite graphite. Both single-particle and secondary-particle graphite are coated with carbon. The carbon coating process is as follows: Material 4 is mixed with a liquid phenolic resin solution (phenolic resin 75wt%, emulsifier gelatin 4wt%, stabilizer sodium carboxymethyl cellulose 1wt%, calcium chloride 0.5wt%, chromium trichloride 0.5wt%, water 19wt%) at a mass ratio of 97:3, and reacted in a reactor at 1800℃ for 2h to obtain the final desired graphite. The negative electrode graphite D50 is 10.5μm (typical value), and the specific surface area is 1.65m 2 / g (typical value). Among them, the mass proportion of single-particle graphite a is 50%, and the mass proportion of secondary-particle graphite (1-a) is 50%; the interlayer spacing d1 of single-particle and secondary-particle graphite is 0.335nm, and the interlayer spacing d2 of carbon coating is 0.360nm; the negative electrode formula is SBR:SP:CMC:Gr=1.8%:0.5%:1.2%:96.5% (that is, the mass fraction b of negative electrode active material is 96.5%). The negative electrode surface density is 82.5±3g / m 2 , cold pressed to 1.60g / m 3 , and the negative electrode sheet is obtained after punching.
[0085] The mass ratio of the first electrolyte VC W1 = 0.5*(1-(d1 / d2)) / (a / (1-a)) = 3.5%, and the total ratio is LiPF6:LiFSI:EC:EMC:DMC:VC:DTD:MMDS = 13:5.5:30:25:20:3.5:1.5:1.5;
[0086] The mass ratio of the second electrolyte VC W2 = (1-(d1 / d2))*(100-b*100) = 24%, and the total ratio is LiPF6:EC:EMC:DMC:VC:LiDFOP:PS = 13:25:20:13:24:2.5:2.5;
[0087] The total amount of electrolyte injection is 17.5g, the first electrolyte injection amount is 14g, and the second electrolyte injection amount is 3.5g;
[0088] When the lithium-ion battery is injected, the first electrolyte is injected first in order. After the first electrolyte is injected, the battery is left standing at a high temperature of 45° C. for 48 hours, formed (consistent with Example 1), left standing at a high temperature of 45° C. for 36 hours, and then the second electrolyte is injected.
[0089] Comparative Example 2-1:
[0090] The positive and negative electrode plates are the same as those in Example 2.
[0091] The electrolyte injection weight is consistent with that in Example 2, which is 17.5 g.
[0092] The electrolyte ratio is
[0093] LiPF6:LiFSI:EC:EMC:DMC:VC:DTD:MMDS:LiDFOP:PS=13:4.4:29:24:18.6:7.6:1.2:1.2:0.5:0.5.
[0094] The comparative example electrolyte is not injected for the second time, and all the electrolyte is injected after the battery core is dried (from the specific quantity, it can be known that the weight of each component of the comparative example electrolyte is consistent with that of the embodiment).
[0095] Comparative Example 2-2:
[0096] The positive and negative electrode plates are the same as those in Example 2.
[0097] The electrolyte injection weight is consistent with that in Example 2, which is 17.5 g.
[0098] Comparative Example 2-2 adopts secondary injection, the injection amount of the first electrolyte is 14g, and the injection amount of the second electrolyte is 3.5g.
[0099] The first electrolyte ratio is
[0100] LiPF6:LiFSI:EC:EMC:DMC:VC:DTD:MMDS=13:5.5:30:26.7:20:1.8:1.5:1.5;
[0101] The second electrolyte ratio is LiPF6:EC:EMC:DMC:VC:LiODFB:PS
[0102] =12:25:33:10:15:2.5:2.5;
[0103] The battery electrical performance and cycle performance results of the battery cell test are as follows: Figures 3-4 shown.
[0104]
[0105] From the comparison between the embodiment and the comparative example, it can be seen that the lithium-ion battery produced by the combination of the electrolyte combination of this embodiment and the secondary injection electrolyte process has greatly improved electrical performance and cycle compared with the lithium-ion battery produced by ordinary primary injection electrolyte and conventional secondary injection electrolyte.
[0106] Embodiment 3:
[0107] Make 5Ah lithium iron phosphate battery cells;
[0108] The positive electrode active material is LFP material, and the positive electrode formula is
[0109] PVDF:SP:CNT:LFP=2.0%:1.5%:0.5%:96%. The positive electrode surface density is 200±3g / m 2 , cold pressed to 2.4g / m 3 , after punching and cutting, the positive electrode sheet is obtained;
[0110] The negative electrode active material uses single-particle and secondary-particle composite graphite. The raw material is needle coke, which is first subjected to airflow milling (crushing) to obtain 5-10μm pretreated particles. The pretreated particles are stirred in a reactor at 250°C for 2h, and then continued to heat to 450°C, and stirred to obtain a material with a particle size of 10-20mm, that is, intermediate material one. The intermediate material one is mechanically ball-milled in a ball mill to produce material two with a particle size of 1-8.5μm, and material two is graphitized at 3000°C to obtain intermediate material three, which is single-particle graphite. Intermediate material three is mixed with asphalt in a mass ratio of 90:10, and the mixed material is reacted in a reactor at 600°C for 3h to obtain material four, which is single-particle and secondary-particle composite graphite. Both single-particle and secondary-particle graphite are coated with carbon. The carbon coating process is as follows: Material 4 is mixed with a liquid phenolic resin solution (phenolic resin 80wt%, emulsifier gelatin 4wt%, stabilizer sodium carboxymethyl cellulose 1wt%, calcium chloride 0.5wt%, chromium trichloride 0.5wt%, water 14wt%) at a mass ratio of 97:3, and reacted in a reactor at 1800℃ for 2.2h to obtain the final desired graphite. The negative electrode graphite D50 is 10.8μm (typical value), and the specific surface area is 1.72m 2 / g (typical value). The mass fraction of single-particle graphite a is 47.5%, and the mass fraction of secondary-particle graphite (1-a) is 52.5%; the interlayer spacing d1 of single-particle and secondary-particle graphite is 0.335nm, and the interlayer spacing d2 of carbon coating is 0.365nm; the negative electrode formula is SBR:SP:CMC:Gr=1.8%:1%:1.2%:96% (i.e., the mass fraction b of negative electrode active material is 96%). The negative electrode surface density is 90±3g / m 2 , cold pressed to 1.60g / m 3 , and the negative electrode sheet is obtained after punching.
[0111] The mass ratio of the first electrolyte VC is W1 = 0.5*(1-(d1 / d2)) / (a / (1-a)) = 4.5%, and the total ratio is LiPF6:LiFSI:EC:EMC:DMC:VC:DTD:FB = 13:5.5:30:24:20:4.5:1.4:1.6.
[0112] The mass ratio of the second electrolyte VC W2 = (1-(d1 / d2))*(100-b*100) = 32.9%, and the total ratio is LiPF6:EC:EMC:DMC:VC:LiDFOP:TMSB = 13:20:16.1:14:32.9:2:2.
[0113] The total amount of electrolyte injection is 17.5g, the first electrolyte injection amount is 14g, and the second electrolyte injection amount is 3.5g;
[0114] When the lithium-ion battery is injected, the first electrolyte is injected first in order. After the first electrolyte is injected, the battery is left standing at a high temperature of 45° C. for 48 hours, formed (consistent with Example 1), and left standing at a high temperature of 45° C. for 36 hours.
[0115] Comparative Example 3-1:
[0116] The positive and negative electrodes are the same as those in Example 3;
[0117] The electrolyte injection weight is consistent with that in Example 3, which is 17.5 g;
[0118] The electrolyte ratio is LiPF6:LiFSI:EC:EMC:DMC:VC:DTD:FB:LiDFOP:TMSB=13:4.4:28:22.42:18.8:10.18:1.12:1.28:0.4:0.4;
[0119] The comparative example electrolyte is not injected for the second time, and all the electrolyte is injected after the battery core is dried (from the specific quantity, it can be known that the weight of each component of the comparative example electrolyte is consistent with that of the embodiment).
[0120] Comparative Example 3-2:
[0121] The positive and negative electrodes are the same as those in Example 3;
[0122] The electrolyte injection weight is consistent with that in Example 3, which is 17.5 g;
[0123] Comparative Example 3-2 adopts secondary injection, the injection amount of the first electrolyte is 14g, and the injection amount of the second electrolyte is 3.5g;
[0124] The electrolyte ratio for the first injection is LiPF6:LiFSI:EC:EMC:DMC:VC:DTD:FB=13:5.5:30:27:20:1.5:1.4:1.6;
[0125] The electrolyte ratio for the second injection is LiPF6:EC:EMC:DMC:VC:LiODFB:PS
[0126] =12:25:33:10:15:2.5:2.5.
[0127] The battery electrical performance and cycle performance results of the battery cell test are as follows: Figures 5-6 shown.
[0128]
[0129] From the comparison between the embodiment and the comparative example, it can be seen that the lithium-ion battery produced by the combination of the electrolyte combination of this embodiment and the secondary injection electrolyte process has greatly improved electrical performance and cycle compared with the lithium-ion battery produced by ordinary primary injection electrolyte and conventional secondary injection electrolyte.
[0130] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A lithium-ion battery electrolyte combination, characterized in that: The lithium-ion battery electrolyte combination is used for secondary injection of a lithium-ion battery, wherein the negative electrode active material of the lithium-ion battery is carbon-coated single-grain graphite and carbon-coated secondary-grain graphite; it comprises a first electrolyte for the first injection and a second electrolyte for the second injection; the first electrolyte and the second electrolyte both contain a lithium salt, a solvent and an additive, and the additive comprises vinylene carbonate; The calculation formula of the mass content of vinylene carbonate (W1) in the first electrolyte is as follows: The calculation formula of the mass content of vinylene carbonate (W2) in the second electrolyte is as follows: Among them, a is the ratio of the mass of single graphite particle to the total mass of single graphite particle and secondary graphite particle, b is the mass fraction of negative electrode active material in the negative electrode slurry when preparing the negative electrode of lithium ion battery, d1 is the interlayer spacing of graphite particles themselves, d2 is the interlayer spacing of carbon coating, and W1<W2.
2. The lithium-ion battery electrolyte combination as claimed in claim 1, characterized in that: The mass of the first electrolyte is 75-90% of the total mass of the first electrolyte and the second electrolyte; Or, the ratio a of the mass of the single graphite particle to the total mass of the single graphite particle and the secondary graphite particle is 35 to 55%; Or, when preparing the negative electrode of the lithium ion battery, the mass fraction b of the negative electrode active material in the negative electrode slurry is 95-97%.
3. The lithium-ion battery electrolyte combination as claimed in claim 1, characterized in that: The lithium salt is selected from at least one of lithium perchlorate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium hexafluorophosphate, lithium trifluoromethanesulfonate, lithium bistrifluoromethanesulfonyl imide, and lithium bis(oxalatoborate); Or, the mass fraction of lithium salt in the first electrolyte is 5 to 15%; Alternatively, the mass fraction of the lithium salt in the second electrolyte is 5 to 20%.
4. The lithium-ion battery electrolyte combination as claimed in claim 1, characterized in that: The solvent is selected from at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, γ-butyrolactone, ethyl acetate, methyl acetate, methyl propionate, propyl propionate or ethyl propionate; Or, the mass fraction of the solvent in the first electrolyte is 30 to 80%; Alternatively, the mass fraction of the solvent in the second electrolyte is 30 to 70%.
5. The lithium-ion battery electrolyte combination as claimed in claim 1, characterized in that: The additives also include other additives, and the other additives are selected from at least one of vinyl sulfate, vinyl sulfite, methylene disulfonate, 1,3-propane sultone, tris(trimethylsilyl)phosphate, vinyl fluorosulfate, fluorobenzene, 1,4-butane sultone, and tris(trimethylsilyl)borate; Or, the mass fraction of other additives in the first electrolyte is 0.1 to 6%; Alternatively, the mass fraction of other additives in the second electrolyte is 0.1-6%.
6. The lithium-ion battery electrolyte combination as claimed in claim 1, characterized in that: The additive of the second electrolyte further includes a lithium salt additive, wherein the lithium salt additive is selected from at least one of lithium difluorooxalatoborate, lithium difluorobisoxalatophosphate, lithium tetrafluorooxalatophosphate, and lithium bis(fluorosulfonyl)imide; Alternatively, the mass fraction of the lithium salt additive in the second electrolyte is 1 to 8%.
7. A secondary liquid injection process, characterized in that: A lithium-ion battery electrolyte combination according to any one of claims 1 to 6 is provided, a first electrolyte is injected into the lithium-ion battery, a first standing is performed, and then formation is performed, a second standing is performed, and a second electrolyte is injected into the lithium-ion battery.
8. The secondary liquid injection process as claimed in claim 7, characterized in that: The temperature of the first standing is 40-45°C and the time of the first standing is 24-48h; Alternatively, the second standing temperature is 40-45° C., and the second standing time is 24-36 h.
9. A lithium ion battery, characterized in that: The lithium-ion battery adopts the secondary injection process described in claim 7 or 8 when injecting electrolyte.
10. The lithium ion battery according to claim 9, characterized in that: The positive electrode active material of the lithium ion battery is lithium iron phosphate.
Citation Information
Cited By
Battery
CN120709453A
A battery
CN120709453B